Teaching english for professional purposes: methodological and organizational issues - Natalia V. Burenina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article gives a detailed analysis of the results of the questionnaires answered by teachers of EPP employed by a Russian university. The survey was done in order to reveal organizational and methodological problems that prevent from a considerable increase of the language competence quality of future specialists at the university. The questions reflected various aspects of the activity of EPP teachers. The first block included the questions that helped build up a social and professional profile of the teacher regarding age parameters, teacher’s experience in the field, academic degrees, university education. The second block of questions was aimed at revealing specificity in teaching EPP with taking into account students’ level of English, number of students, duration of learning English in the curriculum. The survey included the questions that made possible to define the most popular methodological techniques and approaches used, forms of teacher’s activity in the classroom. In order to improve the qualityof the English language education of non-linguistic students via up-dating methodological component, areas in which teachers need professional improvement were defined. A review of related works by Russian methodologists in the field was done at the preliminary stage of examining the problem. The summary of the results achieved concludes the article.